2007
DOI: 10.1364/oe.15.011255
|View full text |Cite
|
Sign up to set email alerts
|

Cryogenic temperature characteristics of Verdet constant on terbium gallium garnet ceramics

Abstract: As the first demonstration of Faraday effect in a TGG ceramics, its Verdet constant at 1053 nm is evaluated to be 36.4 rad/Tm at room temperature which is same as that of the single crystal. In addition, the temperature dependence of Verdet constant is obtained experimentally. At liquid helium temperature, it is 87 times greater than that at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(53 citation statements)
references
References 27 publications
3
48
0
2
Order By: Relevance
“…This is readily confirmed by a comparison with a number of well-known magnetooptic materials. For example, the Verdet constant is equal to 115 rad/T×m for Sn 2 P 2 S 6 crystals [11], 187 rad / T m [13,14]. They are comparable to that obtained for our crystals.…”
Section: Resultssupporting
confidence: 84%
“…This is readily confirmed by a comparison with a number of well-known magnetooptic materials. For example, the Verdet constant is equal to 115 rad/T×m for Sn 2 P 2 S 6 crystals [11], 187 rad / T m [13,14]. They are comparable to that obtained for our crystals.…”
Section: Resultssupporting
confidence: 84%
“…Over the past two decades, several studies have shown that the transparent ceramic may replace its single crystal counterpart because of its excellent properties [9,10] . The TGG ceramic was first reported in 2003 [11] , and recent studies had shown that TGG transparent ceramics exhibited qualities similar to those of single crystals [12,13] . The synthesis of TAG transparent ceramics has also been studied [14] .…”
Section: +mentioning
confidence: 99%
“…These crystals are not convenient due to their ferroelectric properties and, moreover, their growth is more complicated technologically, when compare with the procedures for obtaining the glasses. On the other hand, magnetically ordered solids which are nontransparent in the visible and ultraviolet spectral ranges also belong to the bulk magnetooptic materials [33][34][35][36]. In the present study we report the results of studies for the electrooptic and magnetooptic properties of LiKB 4 O 7 , Li 2 B 6 O 10 , and LiCsB 6 O 10 glasses.…”
Section: Introductionmentioning
confidence: 97%